Percepções sociais sobre a intolerância em relação às religiões de matriz africana. - Oliveira, Jorge Luiz Santos de (2019)
Our research aims to look into the following theme: the religious intolerance practiced by the Universal Church of the Kingdom of God (UCKG) against the african matrix religions (AMR). It was set up as a general objective: Understanding the why of the religious intolerance, practiced by the Universal Church of the Kingdom of God, against the african matrix religions. With the following especific objectives: showing the historic way of the religious intolerance process, developed by the Universal Church of the kingdom of God, against the african matrix religions; identify the impacts of the practice of religious intolerance, along with the cultural and social imaginary; and analise the religious intolerance problem, according to all the content researched, focusing on; the roots of intolerance and the seed of coexistence. The methodology applied was framed in a context of social research, using the qualitative descritive and exploratory research method. The colleced data was done in three consecutive and complementary phases. The first phase, a exploratory bibliografic research was developed. The second, the processing of oral interview techniques and thematic readings were used. The third, the processing and the analisis of all the collected data during the firsts phases. The UCKG followers are intolerant as to the religious denominations, nonetheless this procedure strengthens as to the AMR. This is the outcome of the holy war, set up against the devil and the legion of demons, in which they are identified, analogically, with the spiritual entities that are worshiped in the AMR rituals. Mostly, these believers have little education, that follow their leaders dictate in a fanatic way. The lack of knowledge of the real meanings of the cosmo view of the AMR, by the majority of the non followers of these religions denominations is the most important aspect, for the commom sense generation, in the popular imaginary, that: theses religions practice evil during lifetime, bringing up a religious intolerance feeling. The interreligious dialog practice, among the religious leaderships and expanded to all unconcious society, in order to harmonize the differences and strenghthen similarities, bring up the necessary conditions to the establishment of a religious coexistence.